Unofficial development assistance: A dynamic model of charities' donation income - Wiji Arulampalam; Peter G. Backus; John Micklewright (Institute for the Study of Labor (IZA), 2011)
The empirical literature on the determinants of charities donation income, distinguishing the charitable cause, is small. We extend the literature in several ways. First, we focus on overseas development charities allowing us to give more consideration to the particular characteristics of this cause. Second, we look at the impact of macroeconomic change over a quarter century including changes in household income and in government spending on ODA, as well as 'charity level' variables that earlier authors have considered. Third, we use a general dynamic model and rigorous testing procedures to arrive at our specification. Using a newly assembled long panel of data, we find evidence of a strong, but diminishing fundraising effect. We find no evidence of crowding out by either grants made directly to charities or by changes in the public provision of development funding.
urn:nbn:de:101:1-201104114072
Keywords: L3; D1; D6; F3; 330; charitable giving; overseas development; Spende; Private Entwicklungshilfe; Entwicklungshilfe; Haushaltseinkommen; Makroökonomischer Einfluss; Schätzung; Großbritannien